2004
DOI: 10.1093/bioinformatics/bth118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variance components in gene expression data

Abstract: We applied the linear mixed-effects model to quantify different sources of variation. In the first data set, we found that the between-array variance is greater than the between-section variance, which, in turn, is greater than the within-section variance. In the second data set, for the reference samples, the week-to-week variance is larger than the between-array variance, which, in turn, is slightly larger than the within-array variance. For the test samples, the week-to-week variance has the largest variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…The present analysis used two different samples and two different microarray chips to obtain the individual data points. Criteria to assess chip number has been previously described (Chen et al 2004). Previous studies have demonstrated two chips for each data point, assuming an R 2 O0.95 and confident P!0.05, provide a critical and statistically relevant analysis (McLean et al 2002, Kezele et al 2005, Small et al 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis used two different samples and two different microarray chips to obtain the individual data points. Criteria to assess chip number has been previously described (Chen et al 2004). Previous studies have demonstrated two chips for each data point, assuming an R 2 O0.95 and confident P!0.05, provide a critical and statistically relevant analysis (McLean et al 2002, Kezele et al 2005, Small et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility between replicate chips was determined and an R 2 O0.95 was judged sufficient to allow two chips to be used per data point, with a P!0.05 confidence. The criteria to consider chip number has been previously described (Chen et al 2004).…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
“…In the context of gene expression data, that are usually characterized by relatively high level of noise [36], stability can be considered an important property: how much the characteristics and composition of the discovered clusters hold when perturbation such as added noise, resampling or random projections are introduced? Can we design stability measures to assess the reliability of the discovered clusters?…”
Section: Introductionmentioning
confidence: 99%
“…The effects of various factors (e.g. dye and slide) on the quality of DNA-microarray data have been studied quite extensively albeit for experiments performed with eukaryotic systems [14][15][16][17][18][19][20]. In contrast, no data quality determination has yet been performed on DNAmicroarray data from experiments with bacterial cultures.…”
Section: Introductionmentioning
confidence: 99%